PEMBELAJARAN MENYENANGKAN DALAM E-LEARNING (KLASIBER) PADA MAHASISWA PAI UNIVERSITAS ISLAM INDONESIA - Lukman Lukman; Arif Wijaya (Millah: Journal of Religious Studies, 2016)
This study aims to determine whether  online learning is done in Islamic Education Program of the Faculty of Islamic Studies, Indonesian Islamic University (UII) through cyberclass  already include fun learning principles or not. This study is an evaluative model, to get feedback to improve the quality of online learning. As result,  Fun learning through cyberclass for students still in the bad category. A total of 44.6% of respondents said online courses less enjoyable. Recommendations of this study, the need for training for lecturers in preparing the RPP Online fun-based learning and training e-learning platform Moodle (MEP). This proposal can be done through a trial with the approach of a Research and Development.